(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The research includes both theoretical and practical aspects. The study aims to analyze and measure the relationship between public spending (the approved variable) and the explanatory variables in Malaysia during the time period (1990-2020) by using the Autoregressive Distributed Time Gaps (ARDL) methodology using Time Series Data during the study period. In order to achieve this goal, the theoretical aspect of public spending and its components and limits of public spending was shortened, with the presentation of the economic effects of government spending. In addition to clarifying the relationship between economic variables and public spending in Malaysia, then presenting and analyzing the results of quantitative measurement. The research reached many results, the most prominent of which was the existence of a positive significant relationship between government spending and the variables of total fixed capital formation, public debt and population. And a significant inverse relationship between the dependent variable government spending and GDP growth. As a result of these results that emerged from the standard analysis of the model, it is worthwhile for the study country to adopt ways and methods to reduce government spending rates within the limits of public revenues available to each country. The research aims to analyze the impact of macroeconomic variables on government spending, as well as to evaluate the behavior of government spending in Malaysia.